1990
DOI: 10.1021/ma00209a010
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 NMR relaxation times of a tripeptide methyl ester and its polymer-bound analogs

Abstract: Carbon-13 spin-lattice relaxation times of the tripeptide methyl ester Boc-Gly-Pro-Pro-OMe and its polymer-bound analogues are reported. Line widths of the signals of -carbon atoms of Pro(2) and Pro(3) are also measured and an interpretation of the line broadening is presented. As polymeric macromolecules the following supports were employed: insoluble cross-linked polystyrene (PS), soluble poly(oxyethylene) (POE), and the graft copolymer poly(oxyethylene)-polystyrene-divinylbenzene (POE-PS). The molecular mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…7 An ethanolic solution of poly(ethylene glycol) 300 mono-p-toluene sulfonate (56.75 g, 0.125 mmol) was added to an ethanolic solution of {The IUPAC name for Fmoc-Gly-OH is N-(fluoren-9-ylmethoxycarbonyl)glycine. 4 POP-Sc support 5: 1 1 1 mol% 3, cross-linked with 2 mol% 2 1 (0.1333 g, 0.316 mmol), 2 (0.0024 g, 0.005 mmol), 3 (0.0009 g, 0.003 mmol) and AIBN (0.0004 g, 0.003 mmol) were combined according to GP1 to give, after washing, polymer 5 as a clear gel (0.0665 g, 49%). IR (gel) n max /cm 21 : 3384, 3069, 3025, 2918, 2865, 1652, 1634, 1608, 1581, 1505, 1452, 1096, 1067 and 1036.…”
Section: Poly(ethylene Glycol) 300 Mono-p-toluene Sulfonatementioning
confidence: 99%
See 1 more Smart Citation
“…7 An ethanolic solution of poly(ethylene glycol) 300 mono-p-toluene sulfonate (56.75 g, 0.125 mmol) was added to an ethanolic solution of {The IUPAC name for Fmoc-Gly-OH is N-(fluoren-9-ylmethoxycarbonyl)glycine. 4 POP-Sc support 5: 1 1 1 mol% 3, cross-linked with 2 mol% 2 1 (0.1333 g, 0.316 mmol), 2 (0.0024 g, 0.005 mmol), 3 (0.0009 g, 0.003 mmol) and AIBN (0.0004 g, 0.003 mmol) were combined according to GP1 to give, after washing, polymer 5 as a clear gel (0.0665 g, 49%). IR (gel) n max /cm 21 : 3384, 3069, 3025, 2918, 2865, 1652, 1634, 1608, 1581, 1505, 1452, 1096, 1067 and 1036.…”
Section: Poly(ethylene Glycol) 300 Mono-p-toluene Sulfonatementioning
confidence: 99%
“…To impart aqueous compatibility upon polystyrene-based supports, thus enabling their use in both SPOC and subsequent on-support screening of library molecules, hydrophilic molecules such as poly(ethylene glycol) (PEG) may be grafted onto the support. [4][5][6] TENTA-GEL 4 and ARGO-GEL 5 are two related commercial examples of polystyrene-PEG grafted supports. As an alternative to grafting, we 7 and others 8 have shown that polymerisation of PEG-containing monomers, either with or in the absence of styrene, produces chemicallyfunctionalised supports that have superior organic and aqueous solvent compatibilities to polystyrene-based and polystyrene-PEG grafted supports.…”
Section: Introductionmentioning
confidence: 99%
“…ArgoGel displays similar characteristics to TentaGel yet swells more extensively because of a higher PEG content [39]. The flexible PEG grafts were used to provide a solution-like environment for bound molecules [40,41].…”
Section: Pegylation Of Crosslinked Ps Resins and Their Derivativesmentioning
confidence: 99%
“…A solid‐phase reaction field consists of solvents, reagents, networked polymer chains, reactive sites, and spacers. In general, it is known that the rate of a solid‐phase reaction is closely associated with the diffusion rate of the reagents and reaction products 10–16. However, shaking of the resins by gas bubbling does not affect the rate of reaction.…”
Section: Introductionmentioning
confidence: 99%